EVALUASI EMISI GAS RUMAH KACA WARM MIX ASPHALT METODE LIFE CYCLE ASSESSMENT - Andry Yuliyanto; Galih Rio Prayogi; Deny Syahputra; Kirtinanda P; Ade Candra Kurniawan (Direktorat Bina Teknik Jalan dan Jembatan, 2025)
The Lampung Provincial Road and Construction Agency reported in 2022 that approximately 391.985 km or 23.05% of road infrastructure was damaged. The use of hot mix asphalt (HMA) for road repairs requires high production temperatures, resulting in increased energy consumption, fuel costs, and GHG emissions. Therefore, the environmental impact of road paving should not be ignored. Additives are added to the mixture to lower the mixing temperature, resulting in a mixture known as warm mix asphalt (WMA). In analyzing the potential for environmental impact savings, LCA was used. Inventory data was obtained from previous research literature studies. LCA was conducted based on a gate-to-gate approach that only covered the mixing process at the asphalt mixing plant (AMP). This study aims to determine the potential for energy reduction, fuel consumption savings, GHG reduction, and total cost savings in the alternative use of WMA in provincial road repairs in Lampung Province. Five types of WMA alternatives were considered, namely WMA with Asphamin, Advera, LEA, Sasobit, and Asphaltan additives. The results of the study show that WMA can reduce the mixing temperature and provide energy savings of between 3.15% and 13.65%. From an environmental perspective, WMA also reduces GHG emissions, with a reduction potential of up to 5.00 kgCO₂ per ton of mixture, equivalent to 13.22% compared to HMA. Economically, the use of WMA provides potential production cost savings ranging from 3.05% to 13.22%. Among the five types of additives tested (Asphamin, Advera, LEA, Sasobit, and Asphaltan), the LEA additive proved to be the most environmentally friendly alternative while also providing the greatest energy and cost savings. Kata Kunci: Life Cycle Assessment, Warm Mix Asphalt, Gas Rumah Kaca, Efisiensi Energi. Keywords: Life Cycle Assessment, Warm Mix Asphalt, Greenhouse Gases, Energy Efficiency